ROLE OF ART-PEDAGOGICAL EDUCATION IN PROFESSIONAL BECOMING THE TEACHER - H.Ye. Gribenko (Academy of Cognitive and Natural Sciences, 2007)
In the article describes of the contemporary trends ofperfection o f the art-pedagogical education.